Analysis of Code-Switching from Shazhaniaa Content on Tiktok - Chairunnisa, Yulpa; Zulferdi, Lazuar Azmi (Raja Zulkarnain Education Foundation, 2026)
The phenomenon of code-switching has become a prominent form of linguistic innovation in the digital era, particularly on social media platforms like TikTok. This study aims to analyze the forms, functions, and factors influencing the use of code-switching in TikTok content uploaded by Indonesian creator Shazhaniaa. This study used a descriptive qualitative method, using 43 TikTok captions published between August and September 2025 as data sources. The data were analyzed based on Poplack's classification, which includes three main types of code-switching: intersentential, intrasentential, and tag-switching. The results indicate that the most dominant form of code-switching is intrasentential code-switching, reflecting the creator's linguistic flexibility and high bilingual skills. The primary functions of code-switching include emphasis, social identity, interactional, and affective functions. Furthermore, the use of code-switching was found to play a crucial role in constructing a digital persona, emphasizing an expressive communication style, and strengthening emotional connection with a bilingual audience. Factors influencing the use of code-switching include the socio-digital context, communicative goals, global cultural trends, and psychological factors. Overall, this research confirms that code-switching practices in digital content are not merely linguistic phenomena, but also representations of identity, communication strategies, and forms of cultural negotiation between locality and globality. This study is expected to provide theoretical contributions to the field of digital sociolinguistics and enrich understanding of the dynamics of bilingualism in modern Indonesian online spaces